Respuesta :

Answer:

[tex]x\le \:-1[/tex]

Step-by-step explanation:

[tex]3\left(x-1\right)\le \frac{1}{2}\left(x+1\right)-6[/tex]

[tex]3x-3\le \:-\frac{11}{2}+\frac{1}{2}x[/tex]

[tex]3x\le \:-\frac{5}{2}+\frac{1}{2}x\\[/tex]

[tex]\frac{5}{2}x\le \:-\frac{5}{2}[/tex]

[tex]5x\le \:-5[/tex]

[tex]x\le \:-1[/tex]

x = -1

3(-2) ≤ ½(0) - 6

-6 ≤ 0 - 6

-6 ≤ -6

This is true.

x = -2

3(-3) ≤ ½(-1) - 6

-9 ≤ -½ - 6

-9 ≤ [tex]-\frac{13}{2}[/tex]

This is also true.

Therefore, x ≤ -1.

ACCESS MORE